1998
DOI: 10.1111/j.1600-0560.1998.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Demodex mites in acne rosacea

Abstract: The hair follicle mites Demodex folliculorum and Demodex brevis and their role in the pathogenesis of rosacea have been the subject of much debate in the past. We studied the prevalence of Demodex mites in facial skin biopsies obtained from 80 patients with rosacea, 40 with facial eczematous eruption and 40 with lupus erythematosus discoides. The mite prevalence in the rosacea group (51%) was significantly higher than in the rest of the study population (eczema 28% and lupus discoides 31%). Demodex mites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 10 publications
0
60
0
14
Order By: Relevance
“…Epitel hücreleri ile beslendikleri ve insanlarda cilt hastalıklarına yol açtığı bildirilmiştir (2)(3)(4). Benzer olarak papülopüstüler kafa derisi döküntüleri, pitiriazis folikulorum rosacea, hiperpigmentli yamalar, blefarit, perioral dermatit ya da püstüler folikülit dahil olmak üzere çeşitli cilt hastalıklarıyla ilişkili olabileceği belirtilmiştir (5,6).…”
Section: Introductionunclassified
“…Epitel hücreleri ile beslendikleri ve insanlarda cilt hastalıklarına yol açtığı bildirilmiştir (2)(3)(4). Benzer olarak papülopüstüler kafa derisi döküntüleri, pitiriazis folikulorum rosacea, hiperpigmentli yamalar, blefarit, perioral dermatit ya da püstüler folikülit dahil olmak üzere çeşitli cilt hastalıklarıyla ilişkili olabileceği belirtilmiştir (5,6).…”
Section: Introductionunclassified
“…In humans, Demodex is found in all types of rosacea and is also associated with blepharitis (also observed in the STAT6/ CD28 Ϫ/Ϫ mice), but whether this ectoparasite plays a significant role in the pathogenesis is controversial; in some recent studies the workers have concluded that it is merely a commensal (3,18). Demodex-associated rosacea has also been observed in human immunodeficiency virus-infected patients (17) and other immunocompromised patients (2,22). In temperate regions, the Th2 response is generally considered more harmful than beneficial, since it causes immediate hypersensitivity, whereas in tropical regions it may mediate protection against endemic helminthic parasites.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Demodex spp, kıl follikülleri ve sebase glandlar içerisinde yaşayan asemptomatik saprofitik ektoparazitlerdir (1,2). İnsanlarda Demodex folliculorum (DF) ve Demodex brevis (DB) olmak üzere sadece iki Demodex türü saptanmıştır (1,3).…”
Section: Introductionunclassified
“…Deride sebase gland sayısının ve sebum yapımının belirgin olduğu yüzde en yüksek sayıda bulunur, diğer seboreik alanlarda nadir veya yoktur 6 . Sağlıklı deride enfestasyon oranı yaşla beraber artar ve orta yaş üzerindeki erişkinlerde prevalansı yaklaşık %100 olarak görülür (2,3). Akne vulgaris, ergenlik döneminde baş-layan, foliküler kanalda tıkanmaya bağlı olarak gelişen, yüz başta olmak üzere seboreik bölgelerde; komedon, papül, püstül ve nodüller gibi inflamatuar lezyonlar ile kendini gösteren bir hastalıktır (7).…”
Section: Introductionunclassified